The experiences of Hispanic families of children with autism spectrum disorder regarding physical activity. (December 2020) - Columna, Luis; Felizola, Genesis; Prieto, Laura; Myers, Beth; Streete, Denzil; Lightburn, Anita
Highlights: External barriers played a large role in Hispanic parents engaging their children in physical activity. Parents recognize their integral role in engaging their child in physical activity. Hispanic parents desire qualified physical activity professionals that know how to adapt movement for their children. Hispanic parents may lack information about physical educators' role in providing services to their children. Abstract: Background: Researchers seldom focus on the services needed for Hispanic children with ASD, especially in regard to physical activity (PA). Purpose: The purpose of this study was: (a) to explore why Hispanic families with children with ASD seek out and participate in PA, and (b) to describe the strategies and supports needed by Hispanic families of children with ASD to improve PA participation. Methods: Participants in this descriptive-qualitative study were Hispanic parents of children with ASD (n = 9) who participated in one-on-one semi-structured telephone interviews. Interviews were transcribed and then analyzed using thematic line-by-line analysis. Results: Two major themes emerged from the data: 1) Personal Responsibility and 2) "Every Day is a Different Challenge". Parents were motivated to engage in PA because of perceived health benefits for themselves and their children. Parents faced famililal and external barriers that impacted their participation. Participants commented on the role of culture (e.g., customs, lack of family support after immigration) in the context of these barriers. Implications: Further research is needed regarding culturally responsive PA interventions for Hispanic families with children with ASD.